Dietary carrot consumption and the risk of prostate cancer - Xu, Xin; Cheng, Yunjiu; Li, Shiqi; Zhu, Yi; Xu, Xianglai; Zheng, Xiangyi; Mao, Qiqi; Xie, Liping (European journal of nutrition, 2014)
PURPOSE: Previous studies regarding the association between carrot intake and prostate cancer risk have reported inconsistent results. We conducted a meta-analysis to summarize evidence on this association and to quantify the potential dose–response relationship. METHOD: A systematic literature search of papers published in August 2013 was conducted using PubMed, EMBASE, Scopus, Web of Science, the Cochrane register, and the Chinese National Knowledge Infrastructure databases, and the references of the retrieved articles were screened. The summary risk estimates with 95 % confidence intervals (CIs) for the highest versus the lowest intake of carrots were calculated. A dose–response meta-analysis was also conducted for the studies reporting categorical risk estimates for a series of exposure levels. RESULTS: We found a significantly decreased risk of prostate cancer associated with the intake of carrots (odds ratio 0.82, 95 % CI 0.70–0.97). In addition, the dose–response meta-analysis indicated that for each serving per week, or 10 g per day increment of carrot intake, the risk estimate of prostate cancer was 0.95 (0.90–0.99) or 0.96 (0.94–0.99). There was no evidence of significant publication bias based on Begg’s funnel plot (P = 1.000) or Egger’s test (P = 0.804). CONCLUSION: Carrot intake might be inversely associated with prostate cancer risk. Because of the limited number of cohort studies and substantial heterogeneity observed between studies in this meta-analysis, further well-designed prospective studies are warranted to confirm the findings from our study.